Employee Commitment to Improving Work Performance with Remuneration as a Mediator - Sry Rosita, Dian Mala Fithriani, Fitri Widiastuti (Jurnal Manajemen, 2019)
This study aims to examine employee commitment to improving work performance with remuneration as a mediator variable. The research objects discussed are; 1) Employee commitment, 2) Work performance and 3) Remuneration. The target of the study was 164 Civil Servants at the University of Jambi. The results showed that employee commitment has a greater influence on work performance if mediated by remuneration rather than the direct influence of employee commitment on work performance. This can be interpreted that remuneration which is a performance allowance to employees has a large role as a mediator on employee commitment which shows employee involvement to reach the goal so that it can improve work output which is the achievement of work performance.